Low-temperature supercritical activation enables high-performance detection of cell-free DNA by all-carbon-nanotube transistor. (30th August 2022) - Ren, Qinqi; Zhang, Yaping; Ma, Shenhui; Wang, Xiaofang; Chang, Kuan-Chang; Zhang, Yiming; Yin, Feng; Li, Zigang; Zhang, Min
Abstract: Biosensors based on carbon nanotube (CNT) thin-film transistors (TFTs) have drawn intense interests for their exhibiting great potential in ultrasensitive and label-free DNA detection. However, the inevitable defects in the dielectric and channel of CNT-based TFTs may induce noisy or unreliable output signals. Here, we propose a low-temperature supercritical carbon dioxide (SCCO2 ) fluid activation method to enhance the performance of transistor-based biosensors. An activation model of SCCO2 treatment is proposed to elaborate that the SCCO2 treatment can repair the dangling bonds of SiO2 dielectric facilely and passivate the hydroxyl groups effectively. Furthermore, a cell-free DNA detection platform is built up based on all-carbon-nanotube TFTs (AC-TFTs) modified by the CW-Peptide probe. By adopting the SCCO2 treatment, the response of AC-TFT biosensors to AKT2 gene related to triple-metastatic negative breast cancer can be enhanced by more than 114% with high uniformity, and a broad detection range of six orders of magnitude is yielded with a theoretical limit of detection of 42 fM. Additionally, the response has a linear correlation with the length of DNA targets. The nondestructive and eco-friendly SCCO2 activation method provides a promising and universal strategy for achieving highly accurate and sensitive transistor-based biosensors in future clinical applications. Graphical abstract: Image 1